The role of Symbiotic approaches to socio-cultural change in the Twenty-first Century: The principles and uses of the Symbiotic approach to socio-cultural change - Mandavilli, Sujay Rao (Advances in Social Sciences Research Journal, 2018)
This paper emphasizes the importance and relevance of the proposed Symbiotic school of socio-cultural change in the context of the Twenty-first century. The approaches that we propose may also be referred to as ‘Cultural Osmosis’, and seek to replace older schools and theories of Cultural Change. This would lead to Cultural integration with different cultures still retaining some of their own unique characteristics. The ethics and the pros and cons of activism are also explored, along with their role in aiding cultural remediation. This paper also introduces concepts such as the theory of mind-orientations, the theory of cultural orientations and the theory of Mind space as well. These approaches are expected to integrate with Applied Anthropology and Developmental Anthropology take them to greater heights. We conclude by discussing the potential real-world applications of Symbiotic Models of socio-cultural change.